Complications increase in which type of duodenal diverticulum? A retrospective cohort study - Akaydın, Murat; Akay, Tamer; Leblebici, Metin (Journal of Surgery and Medicine, 2020)
Aim: In endoscopic retrograde cholangiopancreatography (ERCP), a diverticulum increases complications such as perforation and pancreatitis. We must know which type of diverticulum increases the complications to develop a strategy. The aim of this study is to examine the safety of the ERCP procedure in terms of diverticulum types. Methods: A total of 864 patients aged 65 years and over who underwent ERCP from January 2010 to November 2019 were identified and analyzed in this retrospective cohort study. Demographic findings, indications, successful cannulation rates and complications were compared between groups with and without duodenal diverticula. Results: Of the patients who underwent ERCP, 56.4% were female. The mean age of all patients was 77.39 (65-90) years. The most common indications were common bile duct stones (92.1%). Other indications included cholangitis (1.4%), sphincter Oddi dysfunction (1.6%), pancreatitis (2.1%), Mirizzi syndrome (2.7%), postoperative gallbladder fistula (0.7%), periampullary tumor formation (0.57%) and biliary stenosis (0.23%). Among all patients, 848 (98.1%) had no complications, 2 (0.34%) developed pancreatitis, 1 (0.17%) developed cholangitis and bleeding occurred in 1 (0.17%) patient in the group without a duodenal diverticulum. Among patients with a type I diverticulum, 4 (12.9%) had pancreatitis and 3 (9.6%) had bleeding. One patient (1.16%) had pancreatitis, 1 (1.16%) had cholangitis and 2 (2.33%) had bleeding among the type II group, while in the type III group, 1 (0.64%) had pancreatitis and 1(0.64%) had a perforation. Mortality was seen in 2 (0.23%) patients. A total of 5 (0.57%) periampullary tumors were detected in the study. Conclusion: Our study revealed that patients with a duodenal diverticulum experience more complications than the normal population. Among them, the rate is insignificantly increased in those with a type I duodenal diverticulum. Further studies are needed on this subject.